"A community of common descent": Planning the documentation of diaspora through the Electronic Irish Research Experience. Issue 2 (2nd October 2017) - Edwards, Julie Biando; McCrea, Donna E.
ABSTRACT: In 2014, the Maureen and Mike Mansfield Library at the University of Montana–Missoula was awarded a one-year National Leadership planning grant from the Institute of Museum and Library Services (IMLS) to explore the development of EIRE, the Electronic Irish Research Experience. EIRE was conceived as a digital humanities project to address gaps in the scholarship on the Irish in the United States by bringing private and institutional archival collections together online. Throughout the planning year, the Mansfield Library and its partners refined the scope of EIRE, prioritized certain aspects of the project over others, and grappled with questions of sustainability, accessibility, and resource allocation. This article shares our vision, process, results, and lessons learned.